Protection masks with religious motifs: COVID-19 produces new religious materiality - Souza, Patrícia Rodrigues de (International journal of Latin American religions, 2020)
Preventive procedures against COVID-19 pandemic have caused many changes in everyday life’s material aspects. Confinement and social distancing have certainly been the most impacting ones. Such condition highlighted that religions, usually taken as something private and transcendent, are actually very material, in the sense that they are made in contact with and through body practices. The interruption of rituals and gatherings for religious activities prompted new religious material forms, like the use of technology for virtual ceremonies and protection masks adorned with religious motifs, the main point of this paper. Masks with Christian and Afro-Brazilian religious motifs sold on the internet as well as the process of making masks for donation as an unexpected form of religious activity will be here investigated. The goal is to show that material forms are intrinsic to religion and when they are suppressed in a way, they come around in another, for people need materiality to make unreal, real. The use of Material Religion approaches to examine such object should reveal that the many changes in religion triggered by pandemic will have occurred not because of the ideas it may evoke but through the material changes it might have occasioned.